THE DERIVATIVE OF A FUNCTION AND ITS FUNDAMENTAL PROPERTIES - Boboqulova Durdona Sanjar qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This paper explores the concept of the derivative of a function, a cornerstone of differential calculus. The derivative describes how a function changes at any point and serves as a fundamental tool in mathematical modeling, physics, economics, and engineering. The study presents the formal definition of the derivative, rules of differentiation, and key properties such as continuity, monotonicity, and concavity. Applications in real-world contexts are also discussed.